2018
DOI: 10.1038/s41557-018-0042-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization of peptides with two chemical bridges affords large scaffold diversities

Abstract: Successful screening campaigns depend on large and structurally diverse collections of compounds. In macrocycle screening, variation of the molecular scaffold is important for structural diversity, but so far it has been challenging to diversify this aspect in large combinatorial libraries. Here, we report the cyclization of peptides with two chemical bridges to provide rapid access to thousands of different macrocyclic scaffolds in libraries that are easy to synthesize, screen and decode. Application of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
168
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(170 citation statements)
references
References 41 publications
2
168
0
Order By: Relevance
“…Other groups, using display-based technologies, have identified cyclic peptides with low-nanomolar affinities 21 ; these cyclic peptides, however, feature a larger ring structure (up to 14 randomized amino acid positions), and therefore benefit from a higher enthalpic contribution to binding free energy. In other instances, the peptide macrocycle is constrained via multifunctional crosslinkers to increase both the enthalpic and entropic contributions of binding free energy 22 .…”
Section: Binding Affinity Analysis Of Lysozyme Cyclic Peptidesmentioning
confidence: 99%
“…Other groups, using display-based technologies, have identified cyclic peptides with low-nanomolar affinities 21 ; these cyclic peptides, however, feature a larger ring structure (up to 14 randomized amino acid positions), and therefore benefit from a higher enthalpic contribution to binding free energy. In other instances, the peptide macrocycle is constrained via multifunctional crosslinkers to increase both the enthalpic and entropic contributions of binding free energy 22 .…”
Section: Binding Affinity Analysis Of Lysozyme Cyclic Peptidesmentioning
confidence: 99%
“…As described in the introduction, a wide range of reagents containing two thiol‐selective electrophiles, can efficiently cyclize peptides that are terminally flanked with cysteines. Previous work with phage display peptide libraries has shown that peptides with cysteines spaced by only one amino acid (Cys‐Xaa‐Cys) can efficiently be cyclized with bis‐electrophile reagents . A potential challenge was that such reagents could theoretically also react with the DNA, in particular when the reagents had reacted with a first thiol group and the reaction with DNA would happen intramolecularly.…”
Section: Resultsmentioning
confidence: 99%
“…Another option is the introduction of chemical post-translational modifications (cPTM) that can vastly expand the diversity of peptide libraries, for example, by phosphorylation [189], conjugation to glycans [190,191], attachment of a fluorescent reporter [192], or ligation to a synthetic peptide fragment [193]. By introducing constrained topologies, cyclic [194] or bicyclic [195] variants can be generated [187]. However, cPTMs are not quantitative.…”
Section: Incorporating Unnatural Amino Acids and Constraints Into (Limentioning
confidence: 99%